Правовий статус циган у Великому князівстві Литовському - Крумаленко, М. В.; Krumalenko, M. (My University, 2010)
The legal status of gipsy groops is disscused all over European society today. The article is devoted to research of historical roots of forming of legal status of gipsy population on Ukrainian earths. The process of settling gipsy on Ukrainian earths, features that efected their religious world view, the norms of legislation that regulates their legal status in the Grand Duchy of Lithuania, are analysed.
Крумаленко М. В. Правовий статус циган у Великому князівстві Литовському / М. В. Крумаленко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 479-485.
Keywords: Велике князівство Литовське; правовий статус циган у Великому князівстиві Литовському; заселення українських земель циганами; Великое княжество Литовское; правовой статус цыган в Великом княжестве Литовском; заселение украинских земель цыганами; Grand Duchy of Lithuania; the legal status of Roma in the Grand Duchy of Lithuania; Roma population of the Ukrainian lands